One-pot synthesis and applications of two asymmetrical benzoxanthene dyes. (April 2022) - Guo, Yimin; Wang, Xiuping; Liu, Weimin; Zheng, Xiuli; Ren, Haohui; Wu, Jiasheng; Ge, Jiechao; Zhang, Wenjun; Lee, Chun-Sing; Wang, Pengfei
Abstract: Two asymmetrical benzoxanthene dyes (BP-1 and BP-2 ) were designed and synthesized by a convenient one-step procedure from naphthaldehyde and m -aminophenol precursors. These dyes showed long-wavelength absorption, near-infrared emission (>650 nm), and large Stokes shifts (>90 nm) because of the asymmetrical introduction of the benzene ring into the xanthene structure. BP-1 exhibited high fluorescence quantum yield in organic solvents, whereas BP-2 showed very weak fluorescence due to the photoinduced electron transfer of 9-substituted groups. Cell experiments indicated that BP-1 with crescent-shape structure showed lower cytotoxicity and higher photostability than BP-2 and could rapidly stain RNA in nucleoli at low concentration. Graphical abstract: Image 1 Highlights: Two asymmetrical benzoxanthene dyes were synthesized by a convenient one-step procedure. The dyes showed long-wavelength absorption, near-infrared emission and large Stokes shifts. BP-1 could stained RNA in nucleoli rapidly with low cytotoxicity and good photostability. BP-2 showed a very weak fluorescence and cytotoxicity due to 9-substituted groups.